Appropriate cyclic tensile strain promotes biological changes of cranial base synchondrosis chondrocytes. (20th July 2017) - Chu, F.; Feng, Q.; Hu, Z.; Shen, G.
Structured Abstract: Objectives: This study was designed to clarify biological changes of cranial base synchondrosis chondrocytes (CBSCs) upon cyclic tensile strain (CTS) loading which simulated orthopaedic mechanical protraction on cranial base synchondroses (CBS). Material and Methods: A two‐step digestion method was used to isolate CBSCs obtained from 1‐week‐old Sprague Dawley rats. Immunohistochemical staining of type II collagen and Sox9 was conducted to identify chondrocytes. A CTS of 1 Hz and 10% elongation was applied to the second passage of CBSCs by FX‐5000™ Tension System for 24 hours. The control group kept static at the same time. The expression levels of extracellular matrix ( Acan, Col1a1, Col2a1 and Col10a1 ) and key regulatory factors ( Sox9, Ihh and PTHrP ) were detected by quantitative real‐time RT‐PCR. Results: Positive staining of type II collagen and Sox9 was detected in the isolated CBSCs. The relative expression level of Acan, Col2a1, Col10a1, Sox9 and Ihh in the CTS‐loading group was 1.85‐fold, 2.19‐fold, 1.53‐fold, 6.62‐fold, and 1.39‐fold, respectively, as much as that in the control group, which had statistical significance ( P <.05). There was no statistical difference ( P >.05) in the expression of Col1a1 and PTHrP . Conclusions: A CTS of 1 Hz and 10% elongation for 24 hours had positive effects on chondrocyte proliferation, phenotype maintenance and cartilage matrix synthesis.